Electronic Democracy in Ukraine: Institutional Analysis - Savka, Viktor; Myshok, Romana (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper focuses on the differences in interpretation of the institutional theory main terms – «social institution» and «social institute» in Ukrainian and world sociology language. In accordance with the requirements of the sociological methodology (systemic understanding of all social phenomena) and the etymology of these terms, social institutions are treated as balanced systems of component institutes. It is stressed that electronic democracy is a relatively autonomous institute, which is a part of democracy institution structure. In line with this approach, the institute of e-democracy is considered as an integral part of the social institution of democracy, which arises in the modernization process of the institution, its adaptation to the requirements of modern computerized society, and performs certain functions in it, partial tasks in the system of public appointment of the institution of democracy as a whole. E-democracy formation serves not only as a formal sign of the institutional modification, but at the same time it is a qualitative change, a significant transformation of the essential filling of institution. This contributes to the more effective achievement of democracy main purpose: the expansion of citizen participation in the power decisions adoption, and thus stimulate the formation of civil society in modern conditions. At the same time, electronic democracy in Ukraine, which is at an early stage of institutional development, is rather vulnerable, and thus generates a many problems and threats for the institution of democracy and modern society as a whole. They relate primarily to the inadequate accessibility of this tool for the citizens (the socio-cultural dimension of the problem), the complication with effective protection of information dissemination channels (the technical side of the problem), and the counteraction to the consequences of unauthorized interference with the course and direction of democratic procedures (the socio-technical dimension of the problem), and therefore require a proper response from society for these threats.